The bully-proof workplace : essential strategies, tips, and scripts for dealing with the office sociopath - Dean, Peter J., 1946-; Shepard, Molly Dickinson (McGraw Hill Education on BrillianceAudio., 2017)
More than one in four Americans deals with an on-the-job bully. These office sociopaths don't just make individuals miserable. Their poison spreads throughout the company, damaging overall morale, creativity, productivity, and profitability. It doesn't have to be this way.